1984
DOI: 10.1002/art.1780270416
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin in Sjögren's Syndrome

Abstract: The concentration of lactoferrin (LF) in unstimulated mixed saliva in Sjogren's syndrome assayed by a double-antibody solid-phase radioimmunoassay was 16.28 * 3.05 pg/mg of protein (range 7.42-33.64) and differed significantly (P < 0.001) from that of normal control subjects matched for sex and age (2.82 * 0.80 pglmg of protein, range 0. 59-7.35). An unlabeled antibody-enzyme (peroxidase-antiperoxidase) method for labial salivary gland biopsies optimally fixed in Carnoy's fluid yielded strong staining of LF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…An increase in the lactoferrin concentration in saliva from the parotid gland was found by Jezequel et al (20) and by Konttinen et al (21). However, there are conflicting results when it comes to the correlation between the lactoferrin concentration in stimulated parotid saliva and the degree of inflammation in the salivary glands (20, 21). We think it is reasonable to believe that part of the lactoferrin in the primary Sjögren’s syndrome group comes from the inflamed salivary glands and the rest from leakage through disrupted fragile mucosal membranes due to a longstanding low salivary secretion rate.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…An increase in the lactoferrin concentration in saliva from the parotid gland was found by Jezequel et al (20) and by Konttinen et al (21). However, there are conflicting results when it comes to the correlation between the lactoferrin concentration in stimulated parotid saliva and the degree of inflammation in the salivary glands (20, 21). We think it is reasonable to believe that part of the lactoferrin in the primary Sjögren’s syndrome group comes from the inflamed salivary glands and the rest from leakage through disrupted fragile mucosal membranes due to a longstanding low salivary secretion rate.…”
Section: Discussionmentioning
confidence: 67%
“…2). Konttinen et al (21) found a similar increase in lactoferrin concentration in unstimulated whole saliva. An increase in the lactoferrin concentration in saliva from the parotid gland was found by Jezequel et al (20) and by Konttinen et al (21).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These results suggest that a reduction in salivary gland HBD-2 expression occurs earlier than that of HBD-1 during the progression of SS, even though histological differences were not found. The expression of lactoferrin, an antimicrobial protein, was found to be increased in labial glands of subjects with SS (19). This indicates that SS might cause dysfunction to the production of antimicrobial substance.…”
Section: Discussionmentioning
confidence: 91%
“…The expression of lactoferrin, an antimicrobial protein, was found to be increased in labial glands of subjects with SS (19). This indicates that SS might cause dysfunction to the production of antimicrobial substance.…”
Section: Discussionmentioning
confidence: 99%